2002
DOI: 10.1002/1099-0690(200207)2002:14<2331::aid-ejoc2331>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Fusidilactones, a New Group of Polycyclic Lactones from an Endophyte, Fusidium sp.

Abstract: The bicyclic fusidilactones A (1) and B (2) and the structurally unusual fusidilactone C (4) with an oxoadamantane skeleton, a spiro acetal structure and two ether‐bridged hemiacetals were isolated from the fungal endophyte Fusidium sp. (© Wiley‐VCH Verlag GmbH, 69451 Weinheim, Germany, 2002)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(37 citation statements)
references
References 10 publications
0
37
0
Order By: Relevance
“…Endophytic fungi are potential sources of novel natural products, partly due to the richness of hitherto unknown species (sensu Schulz et al 2002;Krohn et al 2002;Tejesvi et al 2007Tejesvi et al , 2009Huang et al 2008). In this study, 33 distinct taxa belonging to a wide range of taxonomic groups were identified from the 18S region of the sequenced isolates.…”
Section: Endophyte Richness and Ecologymentioning
confidence: 99%
See 1 more Smart Citation
“…Endophytic fungi are potential sources of novel natural products, partly due to the richness of hitherto unknown species (sensu Schulz et al 2002;Krohn et al 2002;Tejesvi et al 2007Tejesvi et al , 2009Huang et al 2008). In this study, 33 distinct taxa belonging to a wide range of taxonomic groups were identified from the 18S region of the sequenced isolates.…”
Section: Endophyte Richness and Ecologymentioning
confidence: 99%
“…Endophytes associated with trees are unlikely to include systemic symbionts similar to those found in pooid grasses. However, their diversity, novelty and possible bioactive roles indicate that they are likely to produce various currently unknown metabolites with wide potential applications (Stierle et al 1993;Strobel et al 2004;Huang et al 2008); indeed several interesting substances have already been discovered in rational screenings Krohn et al 2002;Mitchell et al 2008). Trees may also benefit from the presence of endophytes, because they restrict the growth and survival of insect herbivores (see, for example : Carroll 1995;Webber 1981;Saikkonen et al 1996;Faeth and Hammon 1997;Wilson and Carroll 1997), or increase pathogen resistance in the host (Arnold et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Several compounds having the furo[3,4- b ]pyran-5-one bicyclic ring system have been reported from fungi with diverse biological activities, including antibacterial and cytotoxic activities. 2126 …”
mentioning
confidence: 99%
“…Isolation of natural products: biologically active metabolites from phytopathogenic and endophytic fungi of terrestric and marine origin (10, 11). 9,10 In cooperation the chemical constituents of medicinal plant extracts from Africa and Asia are also investigated. Selected publications…”
Section: New Methodology: Transition-metal Catalyzed Oxidations and Rmentioning
confidence: 99%